Analysing the availability and potential utilisation of technology in grade 12 Geography classes in Mankweng Circuit Limpopo Province - Phalane, M. N. (My University, 2020)
The aim of this study was to investigate the availability and potential utilisation of educational technology in the teaching and learning of Geography in Grade 12 in Mankweng Circuit, in the under resourced area of Limpopo Province. The researcher used the constructivist theory with an emphasis upon constructivism as a theoretical framework. A qualitative research approach and a case study design were adopted for this study. Furthermore a purposive sampling strategy was used to sample seven teachers and four principals. In this study all the Secondary Schools fall under Quintile one-the Department of Basic Education’s classification category for no fee paying schools. There are no private or independent high schools that are privately owned, governed or funded in the Circuit. Government has made several attempts to improve the results by providing policies, resources such as infra-structure like classrooms and books, extended additional training of teachers and in some cases, schools took learners to camps for further studies. However, despite these efforts, the problem of the declining of results continues unabated. Data was collected through three methods, namely interviews, observation and document review. Data was analysed through the use of thematic content analysis method. The study came up with three major findings on availability and the use of computers in Grade 12 Geography, namely: (a) inadequate supply of and access to computers in schools and lack of security,(b) Lack of skill on the use of computers by teachers and (c) intermittent power interruptions at these schools influence the performance of learners negatively. These findings have major implications for the use of computers in the teaching of Geography in schools. Firstly, there is an urgent need to supply schools with computers if teachers and learners are to use them to enhance their teaching and learning of Geography and other subjects. Secondly, there is a need to train teachers in the use of computers in the teaching of subjects like Geography otherwise the demands of the Fourth Industrial Revolution will overtake these schools and performance of learners will not improve. Thirdly, principals should attend training workshops to learn about their responsibility as ICT leaders at schools moreover there is a need to tighten security at schools in order to safeguard computers and other valuable equipment that support teaching and learning
Thesis (M.Ed.) -- University of Limpopo, 2020
Keywords: Educational technology; Grade 12; Mankweng Circuit; Information technology -- Study and teaching (Secondary); Educational technology -- South Africa